Study of the influence of stern flaps on the resistance of the high-speed vessels using CFD - ديوب, زين; ميشيل بربهان, (Latakia University Journal -Engineering Sciences Series, 2023)
This study aims to determine the influence of the stern flaps on the hydrodynamic performance of high-speed vessels using CFD (Computational Fluid Dynamic). The URANS method and k-ω Shear Stress Transport (SST) model with ANSYS program were used to solve the Navier-Stokes equations. The Volume of Fluid method was used to capture the free surface and the interaction between the two phases (water, air) around the hull. The comparison between the CFD and Exp-results of total resistance shows a good agreement.